Analisis Kinerja Pelaksanaan Kepmenpan-RB 11 Tahun 2024 Perubahan Nomenklatur Jabatan Pelaksana di Satuan Polisi Pamong Praja Kota Surabaya - Aprilia Tri Wahyuni; Dida Rahmadanik (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research is intended to obtain a real picture of the implementation of non-optimal performance which is driven by an overflow of tasks carried out, thus making work that should be work done wholeheartedly, thereby giving rise to a feeling of workload on the Surabaya City Civil Service Police Unit in order to create an effective and effective organization. efficient. This research uses a qualitative approach with a descriptive research method which aims to describe the problem and focus on the research. The research results showed that: (1) Implementation in accordance with the name of the implementing position in KEPMENPAN No. 11 of 2024 in the civil service police unit through the ABK website platform is still not fully running optimally because its performance is still not optimal, (2) Factors inhibiting the implementation of the implementation according to the name of the implementing position in KEPMENPAN No. 11 of 2024 in the civil service police unit through the ABK website platform are indicators that are considered still low in the policy dimension according to Grindle's theory, including: Program implementation is still not optimal because policy implementation does not have a legal basis such as KEPMENPAN No. 11 of 2024. Apart from that, the civil service police unit does not yet have an SOP regarding managing the crew website in its assignment.